The interplay among COVID-19 economic recovery, behavioural changes, and the European Green Deal: An energy-economic modelling perspective. (15th January 2023) - Cassetti, Gabriele; Boitier, Baptiste; Elia, Alessia; Le Mouël, Pierre; Gargiulo, Maurizio; Zagamé, Paul; Nikas, Alexandros; Koasidis, Konstantinos; Doukas, Haris; Chiodi, Alessandro
Abstract: In the EU, COVID-19 and associated policy responses led to economy-wide disruptions and shifts in services demand, with considerable energy-system implications. The European Commission's response paved the way towards enhancing climate ambition through the European Green Deal. Understanding the interactions among environmental, social, and economic dimensions in climate action post-COVID thus emerged as a key challenge. This study disaggregates the implications of climate ambition, speed of economic recovery from COVID-19, and behavioural changes due to pandemic-related measures and/or environmental concerns for EU transition dynamics, over the next decade. It soft-links two large-scale energy-economy models, EU-TIMES and NEMESIS, to shed light on opportunities and challenges related to delivering on the EU's 2030 climate targets. Results indicate that half the effort required to reach the updated 55% emissions reduction target should come from electricity decarbonisation, followed by transport. Alongside a post-COVID return to normal, the European Green Deal may lead to increased carbon prices and fossil-fuel rebounds, but these risks may be mitigated by certain behavioural changes, gains from which in transport energy use would outweigh associated consumption increases in the residential sector. Finally, the EU recovery mechanism could deliver about half the required investments needed to deliver on the 2030 ambition. Highlights: This study soft-links an energy system model and a macroeconometric model for the EU. Electricity decarbonisation can make up half the effort to −55% followed by transport. Investments as part of EU green recovery could finance about half of what is required. The pandemic is unlikely to heavily impact the EU's long-term emissions trajectory. Work- and travel-related behaviour changes could considerably reduce investment needs.